Regeneration of the Besemah Language as an Effort to Weave Traditions into Digital Media - wita Ita (Utan Kayu Publishing, 2025)
Language and culture are related, as is society. In today's modern era, how the development of language and culture is interdependent and side by side, racing with the flow of technological progress and the development of knowledge. In millennial or urban societies, language and culture are increasingly eroded by the progress of the times (1). Regional languages are valuable assets of a nation, but the 21st century community paradigm considers that foreign languages have higher prestige than national languages and regional languages (2). The urgency of research is a shift in local wisdom, namely the decreasing interest in the use of the Besemah language used by the Besemah tribe in South Sumatra in local content lessons, because the Besemah language is a cultural heritage of the Indonesian nation. However, in the current digital era, the Besemah language faces a serious threat due to the dominance of the Palembang language, Indonesian and foreign languages, especially among the younger generation. With the advancement of technology and globalization, the Besemah language is increasingly being marginalized in everyday life. Therefore, it is important to find ways to preserve and develop the Besemah language by utilizing digital technology as a means that can reach the younger generation and the wider community. There are many factors that cause a language to persist or shift in both minority and immigrant groups (3). The purpose of this study is to identify the challenges and obstacles of the Besemah language in the digital era, and to find effective strategies to utilize technology such as digital media to preserve and develop the Besemah language. While the method used is a qualitative research method (4). With the case study method and digital content analysis. Where data is collected through interviews, observations and document analysis.